Are CEOs Paid for Performance? A Study of CEO’s Compensation in the Public Sector Corporations - Reddy, Krishna (Journal of Economic Analysis, 2023)
This study provides insight into CEO compensation dynamics in the public sector and private sector publicly listed firms in New Zealand. This research uses descriptive statistics, OLS regression, and the difference-in-difference method to analyze the compensation-performance relationship for the period 2005 to 2012. Our findings show that CEOs in the private sector publicly listed firms are receiving higher remuneration benefits. Our results suggest that firm sales and past compensation are the most important determinants of CEO cash-based as well as total compensation. Firms with a larger board size and the presence of a formal remuneration committee are likely to provide higher cash compensation than those without.